Apraxia de fala e apraxia não-verbal na doença de Alzheimer - Cera, Maysa Luchesi [UNIFESP] (2010)
Purpose: to assess the speech and orofacial apraxia in Alzheimer’s disease (AD) and identify praxic speech errors at different stages of the disease and to verify the similarity among their occurrences. Methods: thirty subjects in each stage of AD (mild, moderate and severe) were submitted to the following assessment: Clinical Dementia Rating (CDR), Mini-Mental State Examination (MMSE) and Lawton Instrumental Activities of Daily Living, and praxis tasks, using the oral agility subtest of the Boston diagnostic aphasia examination and the protocol assessment speech and orofacial apraxias. Results: there were 66 women, the mean age was 80,2±7,2 years and means educational was 4,2 ±3,5 years. The means in the oral agility task of AD patients were significantly lower than of the normal population. Difficulties in verbal and nonverbal praxis increased with the progression of the disease. Regarding the types of errors, omission and substitution were more common, followed by trial-and-error, repetition, self-correction and addition. The error type addition determined different patterns of errors between stages of the disease. Conclusions: the speech and orofacial praxias of patients with AD were impaired and deteriorated according to the stage of the disease.